A novel approach to noninvasive monitoring of dissolved carbon dioxide in small-scale cell culture processes - Rahmatnejad, Vida; Tolosa, Michael; Ge, Xudong; Rao, Govind (Frontiers in Bioengineering and Biotechnology, 2022)
Disposable small-scale vessels are commonly used in cell culture studies in academia as well as early stages of bioprocess development. These types of research are crucial for our understanding about cells and bioprocesses as they provide important information regarding different parameters affecting cells. Dissolved carbon dioxide (DCO2) is one main parameter affecting cell metabolism. It is also an indicator of cell culture well-being. Despite CO2 being a critical process parameter, there is a lack of appropriate monitoring system for CO2 in small-scale vessels. Here, we present a membrane-based noninvasive method for measuring DCO2 in cell culture medium. The idea was achieved by modifying a T-flask and replacing a small area of it with CO2 permeable silicone membrane. In the proposed method, the concentration of CO2 dissolved in the cell culture medium is determined by measuring the initial diffusion rate of CO2 through a silicone membrane attached to the bottom wall of the T-flask. The measurement method was validated previously, and the efficacy of the noninvasive method was evaluated by growing E.coli, Pichia pastoris, and CHO cells in the proposed prototype. The results obtained from this method were verified with other quantitative data obtained from the process such as optical density (OD), cell density, dissolved oxygen (DO) and pH. The results show that the proposed membrane-based method is an effective way for completely noninvasive monitoring of DCO2 in small-scale cell culture processes. Additional diffusing species such as oxygen could also be measured using the same approach.